Quality Evaluation of Theses in Teaching Science and Mathematics Program - Prasart Nuangchalerm; Veena Prachagool (Journal of Educational Issues, 2024)
This study aimed to study quality of theses of master education program in teaching science and mathematics, Mahasarakham University, Thailand which conducted and published during 2016-2019. A 37 theses were studied through systematic approach. Data were collected by 24 questionnaires of theses analysis anecdotal. Mean, standard deviation, and percentage were employed. Results showed that most of thesis focus on action research due to the school contexts. Teaching strategies or innovation which employed are problem-based learning, inquiry-based learning, STEM education and other trending approaches. All of informants or samples are studying in high school level. Overall of quality of thesis can be considered in at good level. The finding is useful for program development and shaping research area for graduate students in the future.